HUBUNGAN PERILAKU KONSUMSI MINUMAN BERALKOHOL DENGAN GEJALA GASTRITIS PADA SEKAA TERUNA TERUNI (STT) DI DESA PANGSAN, KECAMATAN PETANG, KABUPATEN BADUNG - I Made Ghora Palguna; Made Oka Ari Kamayani; I Made Suindrayasa (Coping: Community of Publishing in Nursing, 2020)
The influence of globalization is a possible factor that can cause behavior changes in society. One of them is the behavior of consuming alcoholic beverages. There are a lot of negative effects caused for health, one of which is a disturbance in the gastrointestinal system, namely gastritis. The purpose of this study was to determine the relationship between consumption behavior of alcoholic beverages with gastritis symptoms in Sekaa Teruna Teruni in Pangsan Village, Petang District, Badung Regency. The research design uses descriptive correlation design using a cross sectional approach. The research sample used was 84 teenagers. The sampling technique used in this study was the Non Probability Sampling with Quota Sampling technique. The instrument used is a questionnaire. Data analysis method used is spearman correlation using SPSS. In this study, the value of p value <0.05 was obtained which showed that the correlation between alcoholic beverage consumption behavior and gastritis symptoms was significant. The value of the Spearman correlation is obtained at 0.541 which shows a positive correlation with the strength of the medium correlation. so it can be concluded that there is a relationship between the behavior of consuming alcoholic beverages with gastritis symptoms in Sekaa Teruna Teruni in Pangsan Village, Petang District, Badung Regency. Advice for Sekaa Teruna Teruni to control the behavior of consuming alcoholic beverages so that the negative effects such as gastritis can be reduced.